2013
DOI: 10.1186/1471-2458-13-1190
|View full text |Cite
|
Sign up to set email alerts
|

What is actually measured in process evaluations for worksite health promotion programs: a systematic review

Abstract: BackgroundNumerous worksite health promotion program (WHPPs) have been implemented the past years to improve employees’ health and lifestyle (i.e., physical activity, nutrition, smoking, alcohol use and relaxation). Research primarily focused on the effectiveness of these WHPPs. Whereas process evaluations provide essential information necessary to improve large scale implementation across other settings. Therefore, this review aims to: (1) further our understanding of the quality of process evaluations alongs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
220
1
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(251 citation statements)
references
References 77 publications
(238 reference statements)
14
220
1
10
Order By: Relevance
“…The specific components are listed in table 1. Process variables were coded using a list of concepts derived from process evaluation literature (9,11,13,15,17). During coding, the researchers used the list of concepts as a frame of reference, as a starting point.…”
Section: Data Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…The specific components are listed in table 1. Process variables were coded using a list of concepts derived from process evaluation literature (9,11,13,15,17). During coding, the researchers used the list of concepts as a frame of reference, as a starting point.…”
Section: Data Extractionmentioning
confidence: 99%
“…Intervention characteristics were adapted from Murta and colleagues (15). The process evaluation methods components were adapted from Wierenga and colleagues (17). The specific components are listed in table 1.…”
Section: Data Extractionmentioning
confidence: 99%
“…The body of knowledge assessing WHPP's effectiveness is increasing [4][5][6]. A systematic review found more than 300 trials of WHPP published between 2000 and 2012 [5].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review found more than 300 trials of WHPP published between 2000 and 2012 [5]. Still, the effectiveness of such interventions is for several of the targeted lifestyle changes inconclusive or non-consistent [5][6][7][8]. One review even found that high-quality trials tended to report smaller effects than low-quality trials [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation